Srategic Implementation of Sustainable Marketing to Strengthen Brand Image and Customer Loyalty: A Case Study of Garasi Drift - Harnadi, Ziko (Journal Research of Social Science, Economics, and Management, 2025)
This research examines strategic implementation of sustainable marketing to enhance the brand image and customer loyalty to increase the customer loyalty of Garasi Drift automotive lifestyle brand in Indonesia. As the company continues to grow from simply producing content to a multi-division company, selling merchandise and motorsport, it is becoming more important to have a clear and long-term sustainable marketing plan. The research considers a basic problem: What marketing strategy for Garasi Drift is sustainable and how best can it be implemented effectively to strengthen the long-term competitive advantages, customer involvement and differentiation of the brand in an automotive lifestyle automobile sector? The context of this study highlights the rising consumer awareness of sustainability and the shift of automotive lovers toward responsible consumption and the opportunity for digital creators to develop trust-driven and value-oriented brands. This research has a mixed-method approach combining both qualitative and quantitative information obtained from in-depth interviews, customer surveys, internal company information and secondary literature. The research uses the strategic frameworks such as the SWOT analysis, TOWS matrix, and SMART analysis to make strategic recommendations. The results show that sustainable marketing can improve the perception of the brand by ensuring that Garasi Drift’s identity is in line with authenticity, creates long-term value, and has an impact on the community. Strategic opportunities come into play with regard to producing environmentally friendly product lines, using educational content to connect with customers, providing an added value in after-sales, and incorporating sustainability into all areas of the business.